Preparation method of weather-resistant toughened nylon 66 material

By adding nanotitanium dioxide to the nylon 66 material to the modified powder wrapped with fluoropolymer and using gamma ray irradiation technology, the problems of nylon 66 material with high brittleness and poor weather resistance at low temperatures are solved, achieving long-term weather resistance and toughness of the material while meeting the high requirements of emerging industries for material performance.

CN119708832APending Publication Date: 2025-03-28HENAN HAIRUIXIANG TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411759684.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Nylon 66 material absorbs water at low temperatures and is prone to breakage. It also ages and fades, cracks and powders under adverse factors such as light, wind, and rain, which reduces performance and shortens service life. In the prior art, when toughening modification and improving weather resistance, the two often sacrifice each other and are difficult to improve at the same time.

Method used

By adding modified titanium dioxide powder with nanotitanium dioxide as a matrix and wrapped with fluoropolymer on the surface to the nylon 66 material, and using gamma ray irradiation to improve the stability of the coating structure, the long-term weather resistance and toughness of the nylon 66 material are achieved.

Benefits of technology

The advantages of long-term weather resistance and toughness of nylon 66 materials have been successfully achieved, and the rigidity of the material has not been significantly reduced. After long-term use, it still maintains good rigidity and toughness, and has excellent comprehensive performance, meeting the high requirements of emerging industries for the long-term use performance of nylon 66 materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of a weather-resistant toughened nylon 66 material, and relates to the technical field of high polymer material preparation. The method is realized through the following steps: A, preparing modified titanium dioxide powder with a coating structure; b, weighing and mixing; and C, melt extrusion. According to the invention, the modified titanium dioxide powder which takes nano titanium dioxide as a matrix, is coated with the fluorine-containing polymer on the surface and improves the stability of the coating structure by means of gamma ray irradiation is added into the nylon 66 material, so that the long-term weather resistance and toughness of the nylon 66 material are improved at the same time; according to the nylon 66 material, the advantages of long-term weather resistance and toughness of the nylon 66 material coexist successfully, weather-resistant toughening modification of the nylon 66 material is smoothly realized, meanwhile, the rigidity is not obviously reduced, good rigidity and toughness can still be kept after long-term use, the comprehensive performance is excellent, and the high requirement of emerging industries for long-term use performance of the nylon 66 material is met; and development of emerging industries in China is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer material preparation, and more specifically to a method for preparing a weather-resistant toughened nylon 66 material. Background Art

[0002] Nylon has the advantages of high mechanical strength, high softening point, heat resistance, low friction coefficient, self-lubrication, etc. It is the main variety of engineering plastics. But at the same time, nylon also has defects such as high water absorption, poor dimensional stability, poor weather resistance, and poor low-temperature toughness. In particular, water absorption at low temperatures will cause nylon to be brittle and easy to break. In addition, some products will also experience the influence of adverse factors such as light, wind, and rain, aging, fading, and even cracking and powdering, which will reduce performance and shorten service life. Therefore, nylon materials are usually toughened and modified to improve weather resistance. However, in the process of the test, it was found that the toughness and weather resistance of nylon materials are often a trade-off - basically, the toughness of nylon is improved after toughening and modification, while the rigidity is reduced; the rigidity is increased after the weather resistance is enhanced, while the toughness is reduced. Among common materials, fluoropolymers have excellent weather resistance and can work stably in the temperature range of -180℃ to 260℃, showing good high and low temperature resistance. Therefore, adding fluoropolymers to nylon can improve the weather resistance of nylon. However, the compatibility between fluoropolymers and nylon is poor, and the direct addition of fluoropolymers will reduce the toughness and rigidity of nylon. With the rapid development of emerging industries such as new energy vehicles and unmanned aerial vehicles in China, the performance requirements for engineering plastics represented by nylon are getting higher and higher, especially the long-term performance requirements for nylon 66 materials are getting higher and higher. Nylon 66 is one of the most important nylon varieties, accounting for almost half of the total nylon, so the weathering toughening modification of nylon 66 is of great significance to promoting the development of emerging industries in my country. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing a weather-resistant toughened nylon 66 material in view of the deficiencies in the above-mentioned prior art. The present invention adds a modified titanium dioxide powder with nano-titanium dioxide as a matrix and coated with a fluorine-containing polymer on the surface to the nylon 66 material, and uses gamma ray irradiation to improve the stability of the coating structure, thereby achieving simultaneous improvement of the long-term weather resistance and toughness of the nylon 66 material, successfully achieving the coexistence of the advantages of long-term weather resistance and toughness of the nylon 66 material, smoothly achieving the weather-resistant toughening modification of the nylon 66 material, and at the same time, the rigidity does not decrease significantly. After long-term use, it can still maintain good rigidity and toughness, and has excellent comprehensive performance, meeting the high requirements of emerging industries for the long-term use performance of nylon 66 materials, thereby promoting the development of my country's emerging industries.

[0004] The purpose of the present invention can be achieved by the following technical measures: The preparation method of a weather-resistant toughened nylon 66 material of the present invention is achieved by the following steps: A. Preparation of modified titanium dioxide powder with coating structure: A-1. Dissolve the fluorinated polymer and the crosslinking agent in dimethylformamide to form a solution, wherein the mass ratio of the fluorinated polymer, the crosslinking agent, and the dimethylformamide is 100:0.1~5:5000~50000; A-2, adding nano titanium dioxide to the solution obtained in step A-1, stirring at high speed for 60 min to 120 min, and then ultrasonically treating for 30 min to 60 min to obtain a suspension of nano titanium dioxide, wherein the mass percentage concentration of nano titanium dioxide is between 1% and 50%; A-3. Add water to the suspension obtained in step A-2, wherein the weight ratio of the suspension to water is 1:5-100, stir for 30-60 minutes, let stand, separate the layers, and remove the liquid layer; A-4, drying the residue obtained in step A-3, and then irradiating it in a gamma ray radiation field, with an absorbed radiation dose of 50 kGy to 300 kGy; A-5. The irradiated material obtained in step A-4 is crushed by a grinder, and the average particle size of the particles is less than 5 μm, so as to obtain a modified titanium dioxide powder with nano-titanium dioxide as the matrix and a fluorine-containing polymer coated on the surface, and the gamma-ray irradiation is used to improve the stability of the coating structure; B. Weighing and blending: weigh the following raw materials according to the raw material ratio of weather-resistant toughened nylon 66 material, i.e., nylon 66, modified titanium dioxide powder, toughening agent, lubricant, and antioxidant in a mass ratio of 1000:40~100:100~300:2~7:2~7, and then blend them evenly; C. Melt extrusion: Add the uniformly mixed raw materials obtained in step B above into a twin-screw extruder for melt extrusion granulation at an extrusion temperature of 250°C to 280°C to obtain weather-resistant toughened nylon 66 material.

[0005] The fluorine-containing polymer in the present invention is any one of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, polyvinylidene fluoride or a mixture of two or more of them in any proportion.

[0006] The crosslinking agent in the present invention is selected from any one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, di-trimethylolpropane tetraacrylate, and di-pentaerythritol hexaacrylate, or a mixture of two or more in any proportion.

[0007] The toughening agent described in the present invention is a maleic anhydride grafted modified polyolefin elastomer.

[0008] The lubricant described in the present invention is any one of silicone, EBS, polyethylene wax, and PETS, or a mixture of two or more of them in any proportion.

[0009] The antioxidant described in the present invention is selected from any one of antioxidants 168, 1098, 1076, 1010, H11, and S9228, or a mixture of two or more of them in any proportion.

[0010] The design principle of the present invention is as follows: The present invention adds modified titanium dioxide powder with nano-titanium dioxide as a matrix and coated with fluorine-containing polymer on the surface to nylon 66 material, and uses gamma ray irradiation to improve the stability of the coating structure, thereby achieving simultaneous improvement of the long-term weather resistance and toughness of the nylon 66 material, successfully achieving the coexistence of the advantages of long-term weather resistance and toughness of the nylon 66 material, smoothly realizing the weathering toughening modification of the nylon 66 material, and at the same time, the rigidity does not decrease significantly, and after long-term use, it can still maintain good rigidity and toughness, and has excellent comprehensive performance. More specifically, the modified titanium dioxide powder added in the present invention adopts a coating structure of fluorine-containing polymer-coated nano-titanium dioxide because the compatibility of fluorine-containing polymer and nylon 66 material is poor. If the fluorine-containing polymer and nylon 66 material are directly melt-blended, the composite material obtained has poor mechanical properties, unstable weather resistance, and it is difficult to achieve a uniform and stable dispersion effect; while a suspension of nano-titanium dioxide is used, and the fluorine-containing polymer and nano-titanium dioxide are cross-linked and mixed through a gamma-ray radiation field to obtain a fluorine-containing polymer with nano-active groups. Nano-titanium dioxide is an inorganic filling material, and its surface has a very high surface energy and a very high chemical activity. Therefore, under gamma ray irradiation, the fluorine-containing polymer coated with nano titanium dioxide not only ensures the weather resistance of the composite material, but also maintains the excellent comprehensive mechanical properties of the composite material such as good rigidity and toughness, thereby achieving simultaneous improvement of the long-term weather resistance and toughness of nylon 66 material, successfully achieving the coexistence of the advantages of long-term weather resistance and toughness of nylon 66 material, and smoothly realizing the weathering toughening modification of nylon 66 material. At the same time, the rigidity does not decrease significantly, and it can still maintain good rigidity and toughness after long-term use, with excellent comprehensive performance, which meets the high requirements of emerging industries for the long-term performance of nylon 66 material and expands the scope of use of nylon 66 material.

[0011] The beneficial technical effects of the present invention are as follows: The present invention adds modified titanium dioxide powder with nano-titanium dioxide as a matrix and coated with fluorine-containing polymer on the surface to nylon 66 material, and uses gamma ray irradiation to improve the stability of the coating structure, thereby achieving simultaneous improvement of the long-term weather resistance and toughness of the nylon 66 material, successfully achieving the coexistence of the advantages of long-term weather resistance and toughness of the nylon 66 material, smoothly realizing the weathering toughening modification of the nylon 66 material, and at the same time, the rigidity does not decrease significantly, and after long-term use, it can still maintain good rigidity and toughness, and has excellent comprehensive performance, which meets the high requirements of emerging industries for the long-term use performance of nylon 66 materials, thereby promoting the development of my country's emerging industries. DETAILED DESCRIPTION

[0012] The present invention will be further described in conjunction with the following three embodiments: Embodiment 1

[0013] A. Preparation of modified titanium dioxide powder coated with polyvinylidene fluoride on the surface: weigh 100g polyvinylidene fluoride and 2g triallyl cyanurate and dissolve them in 6000g dimethylformamide solvent; then add 300g nano titanium dioxide, stir at high speed for 60min, and then ultrasonicate for 30min to obtain a suspension; add 36000g deionized water to the suspension, stir for 30min and then stand to remove the liquid phase layer, and dry the solid phase layer; put the dried solid into a gamma ray radiation field for irradiation treatment, with an absorbed dose of 50kGy; after the irradiation, crush the solid into a powder with an average particle size of less than 5 microns, and obtain a modified titanium dioxide powder with nano titanium dioxide as the matrix and polyvinylidene fluoride coated on the surface, and the gamma ray irradiation is used to improve the stability of the coating structure for standby use; B. Weighing and blending: Weigh 40 g of the modified titanium dioxide powder coated with polyvinylidene fluoride, and evenly blend it with 1000 g of nylon 66, 100 g of maleic anhydride grafted modified polyolefin elastomer (POE-g-MAH), 2 g of silicone, 1 g of antioxidant 168, and 1 g of antioxidant 1010; C. Melt extrusion: Add the uniformly mixed raw materials obtained in step B above into a twin-screw extruder for melt extrusion granulation at an extrusion temperature of 250°C to 260°C to obtain weather-resistant toughened nylon 66 material.

[0014] The mechanical properties of the weather-resistant toughened nylon 66 material prepared in Example 1 were tested according to the method specified in GB / T 16422.3-1997 "Plastics Laboratory Light Source Exposure Test Method Part 3: Fluorescent Ultraviolet Lamp". The test results are as follows: tensile strength 50MPa, elongation at break 78%, flexural strength 90MPa, flexural modulus 1760.5MPa, notched impact strength 62.8kJ / m 2 . Embodiment 2

[0015] A. Preparation of modified titanium dioxide powder with ethylene-tetrafluoroethylene copolymer coated on the surface: weigh 100g of ethylene-tetrafluoroethylene copolymer and 4g of trimethylolpropane triacrylate and dissolve them in 10kg of dimethylformamide solvent; then add 1000g of nano titanium dioxide, stir at high speed for 100min, and then ultrasonicate for 50min to obtain a suspension; add 100kg of deionized water to the suspension, stir for 40min and then stand to remove the liquid phase layer and dry the solid phase layer; place the dried solid in a gamma ray radiation field for irradiation treatment with an absorbed dose of 150kGy; after the irradiation is completed, crush the solid into a powder with an average particle size of less than 5 microns to obtain a modified titanium dioxide powder with nano titanium dioxide as a matrix and ethylene-tetrafluoroethylene copolymer coated on the surface and gamma ray irradiation to improve the stability of the coating structure for standby use; B. Weighing and blending: weigh 70 g of the modified titanium dioxide powder coated with ethylene-tetrafluoroethylene copolymer, and evenly blend it with 1000 g of nylon 66, 200 g of maleic anhydride grafted modified polyolefin elastomer, 5 g of polyethylene wax, 2 g of antioxidant 1098, and 3 g of antioxidant 1076; C. Melt extrusion: Add the uniformly mixed raw materials obtained in step B above into a twin-screw extruder for melt extrusion granulation at an extrusion temperature of 260° C. to 270° C. to obtain weather-resistant toughened nylon 66 material.

[0016] The mechanical properties of the weather-resistant toughened nylon 66 material prepared in Example 1 were tested in accordance with the method specified in GB / T 16422.3-1997 "Plastics Laboratory Light Source Exposure Test Methods Part 3: Fluorescent Ultraviolet Lamp". The test results showed that the tensile strength was 70 MPa, the elongation at break was 23%, the flexural strength was 120 MPa, the flexural modulus was 2460 MPa, and the notched impact strength was 51.2 kJ / m2. Embodiment 3

[0017] A. Preparation of modified titanium dioxide powder coated with fluorinated ethylene propylene copolymer: 100g of fluorinated ethylene propylene copolymer and 5g of trimethylolpropane trimethacrylate were dissolved in 12kg of dimethylformamide solvent; 2000g of nano titanium dioxide was added, stirred at high speed for 120min, and then ultrasonicated. The suspension was treated with a wave for 60 minutes to obtain a suspension; 200 kg of deionized water was added to the suspension, stirred for 60 minutes and then allowed to stand to remove the liquid phase layer and dry the solid phase layer; the dried solid was placed in a gamma ray radiation field for irradiation treatment with an absorbed dose of 300 kGy; after the irradiation, the solid was crushed into a powder with an average particle size of less than 5 microns to obtain nano titanium dioxide coated with fluorinated ethylene propylene copolymer, and a modified titanium dioxide powder with nano titanium dioxide as a matrix and fluorinated ethylene propylene copolymer coated on the surface and gamma ray irradiation to improve the stability of the coating structure was obtained for standby use; B. Weighing and blending: Weigh 100 g of the modified titanium dioxide powder coated with fluorinated ethylene propylene copolymer, and evenly blend it with 1000 g of nylon 66, 300 g of maleic anhydride grafted modified polyolefin elastomer, 7 g of polyethylene wax, 3 g of antioxidant H11, and 4 g of antioxidant S9228; C. Melt extrusion: Add the uniformly mixed raw materials obtained in step B above into a twin-screw extruder for melt extrusion granulation at an extrusion temperature of 270° C. to 280° C. to obtain weather-resistant toughened nylon 66 material.

[0018] The mechanical properties of the weather-resistant toughened nylon 66 material prepared in Example 3 were tested according to the method specified in GB / T 16422.3-1997 "Plastics Laboratory Light Source Exposure Test Method Part 3: Fluorescent Ultraviolet Lamp". The test results are as follows: tensile strength 70MPa, elongation at break 25.5%, flexural strength 120MPa, flexural modulus 2450MPa, notched impact strength 65.2kJ / m 2 .

Claims

1. A method for preparing a weather-resistant toughened nylon 66 material, characterized in that: The preparation method is achieved by the following steps: A. Preparation of modified titanium dioxide powder with coating structure: A-1. Dissolve the fluorinated polymer and the crosslinking agent in dimethylformamide to form a solution, wherein the mass ratio of the fluorinated polymer, the crosslinking agent, and the dimethylformamide is 100:0.1~5:5000~50000; A-2, adding nano titanium dioxide to the solution obtained in step A-1, stirring at high speed for 60 min to 120 min, and then ultrasonically treating for 30 min to 60 min to obtain a suspension of nano titanium dioxide, wherein the mass percentage concentration of nano titanium dioxide is between 1% and 50%; A-3, add water to the suspension obtained in step A-2, wherein the weight ratio of the suspension to water is 1:5~100, stir for 30min~60min, let stand, separate into layers, and remove the liquid layer; A-4, drying the residue obtained in step A-3, and then irradiating it in a gamma ray radiation field, with an absorbed radiation dose of 50 kGy to 300 kGy; A-5, the irradiated material obtained in step A-4 is crushed by a grinder, and the average particle size is less than At 5 microns, a modified titanium dioxide powder is prepared, which is based on nano titanium dioxide and coated with a fluorine-containing polymer on the surface, and the stability of the coating structure is improved by gamma ray irradiation. B. Weighing and blending: weigh the following raw materials according to the raw material ratio of weather-resistant toughened nylon 66 material, i.e., nylon 66, modified titanium dioxide powder, toughening agent, lubricant, antioxidant in a mass ratio of 1000:40~100:100~300:2~7:2~7, and then blend them evenly; C. Melt extrusion: Add the uniformly mixed raw materials obtained in step B above into a twin-screw extruder for melt extrusion granulation at an extrusion temperature of 250°C to 280°C to obtain weather-resistant toughened nylon 66 material.

2. The method for preparing a weather-resistant toughened nylon 66 material according to claim 1, characterized in that: The fluorine-containing polymer is selected from any one of polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymer, fluorinated ethylene-propylene copolymer, and polyvinylidene fluoride, or a mixture of two or more of them in any proportion.

3. The method for preparing a weather-resistant toughened nylon 66 material according to claim 1, characterized in that: The crosslinking agent is selected from any one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, di-trimethylolpropane tetraacrylate, and di-pentaerythritol hexaacrylate, or a mixture of two or more in any proportion.

4. The method for preparing a weather-resistant toughened nylon 66 material according to claim 1, characterized in that: The toughening agent is maleic anhydride grafted modified polyolefin elastomer.

5. The method for preparing a weather-resistant toughened nylon 66 material according to claim 1, characterized in that: The lubricant is selected from any one of silicone, EBS, polyethylene wax, and PETS, or a mixture of two or more of them in any proportion.

6. The method for preparing a weather-resistant toughened nylon 66 material according to claim 1, characterized in that: The antioxidant is selected from any one of antioxidants 168, 1098, 1076, 1010, H11, and S9228, or a mixture of two or more of them in any proportion.

Citation Information

Cited By

  • Method for preparing high-strength wear-resistant nylon 66 material

    CN120464190A

  • A method for producing a high-strength wear-resistant nylon 66 material

    CN120464190B